PENANGKAPAN IKAN KARANG OLEH NELAYAN LOKAL BERDASARKAN â€œMAKANAN KEBIASAANâ€ DI TAMAN NASIONAL BUNAKEN, MANADO - Farnis Boneka (EKOTON, 2014)
Population of coral polyp eaters such as Acanthaster planci and Drupella cornus increases in Bunaken National Park recently. It might be related to increasing fishing intensity around coral reefs which may reduce fish predators. The objective of the present research is to inventory fishes catched by local fishermen and to describe feeding categories of fish for tracing predation source. Fish were bough from local fishermen between May-July 2008, brought to the marine laboratory for stomach analysis. Feeding categories of fish were analyzed based on food items. A numbers of 69 fish species obtained by means of spear gun (jubi), hand-line (pancing) and gill net (soma, jaring insang). About 42,03 % of fish were carnivores, 30.44% herbivores and 27.53% omnivores. Carnivore fish catched around Bunaken National Park consit of Labridae, Carangidae, Serranidae, Lethrinidae, Sillaginidae, Nemipteridae, Apogonidae, Muraenidae, Pinguipedidae. Omnivores are Balistidae, Lutjanidae and Monochantidae. Food items identified mainly crustacean, polychaetes, fish and mollusk shells. There has not been found fractions of both coral polyp predators on the fish stomachs. Predation on D. cornus and A. plancii may occur during the larval stage.